2013
DOI: 10.3758/s13428-013-0391-5
|View full text |Cite
|
Sign up to set email alerts
|

Global self-esteem and method effects: Competing factor structures, longitudinal invariance, and response styles in adolescents

Abstract: The Rosenberg Self-Esteem Scale (RSES) is a widely used measure for assessing self-esteem, but its factor structure is debated. Our goals were to compare 10 alternative models for RSES; and to quantify and predict the method effects. This sample involves two waves (N=2513 ninth-grade and 2370 tenth-grade students) from five waves of a school-based longitudinal study. RSES was administered in each wave. The global self-esteem factor with two latent method factors yielded the best fit to the data. The global fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 44 publications
5
31
0
4
Order By: Relevance
“…Self-worth was assessed by the Hungarian version of the Rosenberg’s Self-Esteem Scale (RSES-HU; [46], Hungarian version, [47]). The RSES assessed global self-esteem (i.e., feeling of self-worth and self-acceptance) with 10 items on a 4-point scale (“strongly agree” to “strongly disagree”).…”
Section: Methodsmentioning
confidence: 99%
“…Self-worth was assessed by the Hungarian version of the Rosenberg’s Self-Esteem Scale (RSES-HU; [46], Hungarian version, [47]). The RSES assessed global self-esteem (i.e., feeling of self-worth and self-acceptance) with 10 items on a 4-point scale (“strongly agree” to “strongly disagree”).…”
Section: Methodsmentioning
confidence: 99%
“…They found that it demonstrated good internal reliability and factor structure across many languages and different cultures. However, several studies have described variations in interpretation of the negatively worded items, which raises the question of how self-esteem is evaluated in different cultures (Brown, Cai, Oakes, & Deng, 2009; Schmitt & Allik, 2005; Urbán, Szigeti, Kökönyei, & Demetrovics, 2013; Wu, 2008). Taking into account cultural norms and capturing the specifics of the target population became relevant to successfully implementing the study.…”
mentioning
confidence: 99%
“…Unfortunately, a review of the literature does not support these assertions. However, responses to negatively worded items have been found to yield systematic variance that is irrelevant to the content under study, this is irrespective of the age group but it is more commonly with young children (e.g., Benson and Hocevar 1985;Hooper et al 2013;Urbán et al 2014;Marsh 1986). Marsh and his colleagues define method effects as "nontrait effects associated with idiosyncratic aspects of particular items or methods of data collection" (Marsh et al 2013, p. 112).…”
Section: Methods Effects: the Negative Item Effectmentioning
confidence: 99%